Influence of the Surrounding Environment Steam Power Plant (PLTU) Kema Satu Village, Kema District, North Minahasa District - Leony A Wenno; Maya E.I Munaiseche; Laela Worotikan; Sheva B Lahete; Riski Gunawan; Edna T Lontaan; Ni Made Miniari; Gregoryan Anggreyno; Yeko Tabuni (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
In today's era, it is important to understand the impact of Steam Power Plant (PLTU) operations on the environment and economy around the plant site, especially in Kema Satu Village. PLTUs, which harness the kinetic energy of steam from geothermal heat, are widely used due to their ease of operation and accessibility of fuel. However, they also have significant impacts, both positive and negative, on local communities. This study aims to assess the environmental and economic impacts of PLTU Sulut 3 on the surrounding area, evaluate its operational efficiency, and determine its contribution to stabilizing and improving electricity supply in North Sulawesi and Gorontalo. The research method used was a combination of qualitative and quantitative techniques to ensure a comprehensive analysis. Data was collected through observation, interviews, and analysis of relevant secondary data. The results show that the PLTU in Kema Satu Village has significant impacts on the local environment, including air and water pollution, soil degradation, and ecosystem disruption. In addition to providing electricity supply and employment opportunities for the local community, the PLTU has also triggered property price inflation and shifts in the local economy. Other negative impacts include damage to the local agricultural sector and increased greenhouse gas emissions. The implications of this study emphasize the need for careful planning, community involvement, and the implementation of sustainable practices to mitigate negative effects on residents and the environment.